Implementasi Kurikulum Merdeka dalam Pembelajaran Bahasa Arab: Studi Kasus di SDIT Anak Sholeh Praya - Fitriani, Namiyah; Hermawan, M Khaerul; Azizah, Zuyyina Ilmy; Anshori, Muhammad Ridho; Handayani, Rima Ayu (Program Studi Pendidikan Bahasa Arab, 2025)
This study aims to analyze the implementation of the Merdeka Curriculum in Arabic language learning as a local content subject at SDIT Anak Sholeh Praya. The analysis focuses on aspects of planning, execution, supporting and inhibiting factors, as well as curriculum implementation evaluation. Theoretically, this research employs the perspective of Arabic language learning theory for children (Al-'Athiyah li al-Athfal) which emphasizes a contextual approach, combined with the flexibility principles of the Merdeka Curriculum. The research method used is qualitative with a case study approach. Data collection techniques were conducted through in-depth interviews and document analysis, while data analysis utilized the interactive model of Miles and Huberman. The results reveal a paradox where curriculum flexibility actually becomes an additional burden for teachers due to lack of training and systemic support. The main challenges faced include limited teaching time and lack of an environment supporting Arabic language practice. Theoretically, this study provides a critical perspective on the importance of building an equitable support ecosystem in curriculum implementation. Practically, the research recommends developing inclusive mentoring models and equitable resource allocation for local content subjects. The study concludes that successful curriculum implementation requires comprehensive and thorough systemic support. Keywords: Arabic Language, Merdeka Curriculum, Local Content, Curriculum Implementation.